XBeachG Storm Surge Modelling at Blakeney Point, UK - James Alastair Pollard; Elizabeth K Christie; Thomas Spencer; Susan M Brooks (PANGAEA, 2021)
XBeachG outputs from storm surge modelling conducted at Blakeney Point, North Norfolk, UK. – The excel document contains two tabs: README - provides column descriptions for the remaining two tabs. RawData - Eighteen unique profiles were modelled, with ten runs per profile, for four future sea level rise scenarios: 2013 (present, no sea level rise), and a low, moderate, and high sea level rise scenario. This results in a dataset comprising 720 individual model runs. Each row represents one run as is described in the README tab. – The methodology used to generate this data set is described in: Pollard, J.A., Christie, E.K., Spencer, T., and Brooks, S.M. 2021. Gravel barrier resilience to future sea level rise and storms.